“Your subtitles will look like this”: Exploring user preferences for closed captions across streaming platforms - Gabriele Uzzo (Translation and Interpreting : the International Journal of Translation and Interpreting Research)
In recent years, the rise of streaming platforms and Over-The-Top (OTT) services has redefined the landscape of audiovisual content consumption, introducing a wealth of entertainment options that encompasses not only dubbed and subtitled versions but alsocaptioned and audio-described materials. A key trend among most Video on Demand (VoD) and OTT platforms is the availability of customisable subtitle options, as noted by Bucaria (2021). These features enable users to tailor their viewing experience according to individual preferences, reflecting the growing emphasis on personalisation as a crucial aspect of user interaction (Sanchez, 2015). This adaptability allows viewers to modify parameters such as font, size, colour, and background, contributing to a more comfortable and engaging viewing experience. However, the linguistic and paralinguistic attributes of subtitles typically follow the specific guidelines set by each platform.Drawing on validated reception studies in this field, this article examines the complex relationship between stylistic choices in closed captions (CC) among the Italian d/Deaf and Hard of Hearing (DHH) community. Todo so, a comprehensive questionnaire was designed to gauge the nuanced preferences and levels of satisfaction among DHH users, exploring whether particular CC styles are preferred and to what extent the varied landscape of OTT platforms influences contentengagement. The responses, collected from 139 individuals within the Italian DHH community, provide a robust dataset for both quantitative and qualitative analysis. This data serves as a foundation for evaluating user needs and shaping recommendations for the optimal design and presentation of subtitles.